(untitled) (New Jersey, 2004)
The 2004 Asian International Workshop on Advanced Reliability Modeling is a symposium for the dissemination of state-of-the-art research and the presentation of practice in reliability engineering and related issues in Asia. It brings together researchers, scientists and practitioners from Asian countries to discuss the state of research and practice in dealing with reliability issues at the system design (modeling) level, and to jointly formulate an agenda for future research in this engineering area. The proceedings cover all the key topics in reliability, maintainability and safety engineering, providing an in-depth presentation of theory and practice
Keywords: Reliability (Engineering),Computer networks,Kỹ thuật mạng máy tính; Mathematical models,Reliability